METABOLIC FATE OF DIETARY NON-PROTEIN NITROGEN IN HETEROPNEUSTES FOSSILIS (BLOCH) - Mukhopadhyay, Pratap K; Dehadrai, Padmakar V (Indian Journal of Fisheries, 2011)
The metabolic fate of non-protein nitrogen (NPN) from urea as componentof supplementary diet was investigated in the catfish Heteropneustes fossilis.Urea substitution (3% by weight of food), replacing approximately one-fifth ofdietary protein (8.6 g protein s 1.38 g N r ) , registered a better growth performance.An increased intestinal urease activity could be recorded from urea-diet treatment.The activities of liver arginase, alanine aminotransferase and aspartate aminotransferasetogether with the level of blood urea were also studied in response toNPN-diet treatment. All these indicated possibilities of NPN assimilation. Again,the bioconversion of dietary NPN to tissue protein was ascertained by mass spectrometricstudies. No gross change in food value was observed when the fish wasfed on the NPN diet over a rather prolonged period